The learning result of visual art subject for grade 2 students by lesson study and open approach - Prasetsang, Chitipat; Piasiri, Siripong (Journal for Developing the Social and Community, 2022)
The purposes of this research were: 1) to study the results of learning management visual arts course of grade 2 students using classroom education 2) To study the satisfaction of grade 2 students using classroom education and open learning management. research model Qualitative Research using classroom education and open learning management The target group of Prathomsuksa 2 students at Nong Kung Wittayakarn School, Muang District, Khon Kaen Province Khon Kaen Primary Educational Service Area Office, Region 1, 2nd semester, Academic Year 2020, consisted of 7 students by using a specific method. research tools learning management plan The visual arts course consisted of 4 plans. The instrument used to collect data was the satisfaction assessment form of learners towards the learning management of visual arts courses of primary grade 2 students using classroom education. and open learning management The data were analyzed using mean, percentage and standard deviation. The results showed that 1) The result of learning management in visual arts course of students in grade 2 by studying classes and open methods It was found that by using classroom and open learning approaches, students can gain a better understanding of the visual arts creation and the sequential explanation of their work in order to achieve Understanding in class and enabling students to apply their knowledge to develop appropriately and creatively in current problem situations. This can enable teachers to learn about the behavior and creative processes of students in solving problems, as well as being used as a guideline for developing learning activities in the future as well. 2) Assessment results of satisfaction with learning management in visual arts course of grade 2 students by studying the classroom and the open method. Most of the students had a very good level of satisfaction (X ̅ = 4.81, S.D.=0.170).